2023
DOI: 10.3390/ijms24032817
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transient Hypothyroidism in Children Diagnosed with Congenital Hypothyroidism between 2000 and 2016

Abstract: Newborn screening (NBS) for congenital hypothyroidism (CH) was introduced in Switzerland in 1977, which allowed for the preclinical, biochemical diagnosis. The aim of this study was to evaluate the prevalence of transient CH (tCH) in the canton of Zurich. In this analytical cohort study, all newborns born in the canton of Zurich, between the 1st of January 2000 and the 30st of June 2016, with a TSH value above 15 mU/L (whole blood) were included. There were 115 cases out of 247,918 babies born during the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In another study in Fars province, this rate was reported to be 1:313.66 from 2013 to 2016 (30). The overall incidence of CH was reported as 1:2695 in Zurich (31) and 1:2000-1:4000 worldwide (4,31). The prevalence of this disease in Iran is estimated to be higher than in other countries (4), which can be related to the relatively higher prevalence of iodine deficiency, especially moderate iodine deficiency, among Iranian pregnant women since 1968 (32).…”
Section: Discussionmentioning
confidence: 95%
“…In another study in Fars province, this rate was reported to be 1:313.66 from 2013 to 2016 (30). The overall incidence of CH was reported as 1:2695 in Zurich (31) and 1:2000-1:4000 worldwide (4,31). The prevalence of this disease in Iran is estimated to be higher than in other countries (4), which can be related to the relatively higher prevalence of iodine deficiency, especially moderate iodine deficiency, among Iranian pregnant women since 1968 (32).…”
Section: Discussionmentioning
confidence: 95%
“…[5] The incidence of CH was found to be 1:2695 in the canton of Zurich, Switzerland, 1:2783 in Finland, 1:3338 in Germany, and 1:990 in the Apulia region of Italy. [10–13] In Japan, the incidence of CH was reported to be one in 2000 to 2500 births in the 2000s, which was approximately 2 times higher than that in the 1990s. [14] In a study conducted in Shahre-Kord, Iran, the prevalence of CH was 1:500.…”
Section: Discussionmentioning
confidence: 99%
“…In problematic cases more frequent visits are recommended, and during these visits, serum fT4 and TSH levels are monitored. 1,15 One or two control visits within the first week are recommended for patients who have started therapy with higher doses. 17, 19 A moderate range of fT4 levels and TSH levels below 6 mU/L indicate the adequate dose of therapy, while a TSH level below 0.8 mU/L indicates a higher dose.…”
Section: Diagnostic Studies Treatment and Monitoringmentioning
confidence: 99%
“…Congenital hypothyroidism is a global problem with a prevalence between 1/3,000 and 1/4,000. 1 The incidence of this condition is increasing due to environmental factors and the implementation of screening programs. 2 Early diagnosis through heel lance screening programs and prompt initiation of treatment have significantly reduced the cognitive effects of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%